INTERVENCIONES URBANAS POR EL DERECHO A LA CIUDAD - Fuentes, Pedro (2015)
Traditional urban planning, the approach known as “top-down,” coupled with the neoliberal policies of urban development produced a series of phenomena including the emergence of new urban centers, a vibrant culture of fear, privatization of public space, and cities designed with the automobile as a central focus. These effects had a number of significant impacts on the quality of urban life in Latin America, thus causing the decline of the “Right to the City” in San José. “Ciudad Alterna” means Alternate City. Ciudad Alterna is a group of architects who seek to encourage critical thinking about the current dehumanization surrounding urban dynamics through: disobedient action posed by tactical urbanism, guerrilla marketing, and small-scale urban intervention. Realizing the possibilities offered by these tools to reclaim the right to the city requires a direct democracy wherein citizens engage actively in the collective search for solutions regarding situations of social struggle, mobility, and the use and transformation public space in the city of San José, Costa Rica.